The Effect of Digital Literacy and Writing Skills on The Skills of Developing Teaching Materials for Prospective Teacher Students - Emidar; Indriyani, Vivi; Gustia Ningsih, Ayu (Graduate Program Magister Manajemen Pendidikan, 2023)
Instructional materials are an essential component of the learning process. The use of instructional materials can be tailored to students; requirements and characteristics. Prospective instructors must take courses on the development of teaching materials in order to acquire the skills necessary to create instructional materials. To have the skills to develop teaching materials, other skills are needed to support this, including digital literacy and writing skills for prospective teacher students. The purpose of this study was to determine the effect of digital literacy and writing skills on the skills of developing teaching materials for prospective teacher students. This study uses quantitative research methods using causal associative research, namely research that seeks the influence of one variable (independent) with other variables (dependent). The population of this study were 210 students of the Indonesian Language and Literature Education Study Program at UNP BP 2020. The sample selection technique uses purposive sampling. The number of samples obtained were 35 students. The research instrument is in the form of teaching material products, performance tests. Assessment is carried out with the help of an assessment rubric. The data analysis method uses SPSS with the Multiple Regression analysis method. The results of the study show that digital literacy and writing skills have a significant effect on the skills of developing teaching materials for prospective teacher students both collectively and individually.